2018
DOI: 10.1177/2474126418756404
|View full text |Cite
|
Sign up to set email alerts
|

Acute-Onset Postoperative Endophthalmitis in Silicone Oil–Filled Eyes Managed With Intravitreal Antibiotics Alone

Abstract: Endophthalmitis in postoperative silicone oil-filled eyes is rare. The traditional management of these eyes is a return to the operating room for oil removal, instillation of intravitreal antibiotics, and reinjection of silicone oil. We describe 2 cases of endophthalmitis successfully treated with an office injection of intravitreal antibiotics. In both eyes, there was a prompt resolution of endophthalmitis with no apparent signs of retinal toxicity and with favorable visual outcomes. These are the first cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Only five reports of post-PPV endophthalmitis with positive cultures can be found in the existing literature. 5–7,9,10 Chong et al 5 reported a case of post-PPV endophthalmitis caused by Pseudomonas aeruginosa . They observed that clear silicone oil with white material covered the retinal surface of the affected eye.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only five reports of post-PPV endophthalmitis with positive cultures can be found in the existing literature. 5–7,9,10 Chong et al 5 reported a case of post-PPV endophthalmitis caused by Pseudomonas aeruginosa . They observed that clear silicone oil with white material covered the retinal surface of the affected eye.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional therapeutic management for postoperative endophthalmitis consists of silicone oil removal, intravitreal antibiotic injection, and reinjection of silicone oil. [5][6][7][8] Steinmetz et al 8 reported two cases of endophthalmitis in silicone oil-filled eyes, which were treated with antibiotic injection alone. However, whether these cases were truly infectious cases or just severe cases of postoperative inflammatory reaction to the silicone oil is not certain because vitreous or aqueous samples were not collected in one of the cases, and there was no culture growth in the aqueous sample of the other case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Steinmetz et al . [ 13 ] reported two cases of endophthalmitis in siliconefilled eyes that were treated with antibiotic injection alone. However, it was uncertain if these cases were truly infectious or just a severe postoperative inflammatory reaction to the silicone oil, as one of their cases did not have vitreous or aqueous samples, and the other case did not have growth of the aqueous sample.…”
Section: Discussionmentioning
confidence: 99%